MULTIVARIATE ANALYSIS OF BALI SALAK CULTIVARS (SALACCA ZALACCA VAR. AMBOINENSIS (BECC.) MOGEA) BASED ON LEAF MICROMORPHOLOGICAL CHARACTERS - GARI, NI MADE (2011)
Keywords: multivariate analysis; Salacca zalacca var. Amboinensis; taxonomic implication; leaf epidermis

(untitled) (Jurnal Biologi Udayana, 2011)
Leaf micromorphology of 13 Bali salak cultivars was studied by using multivariate analysis (Principal component analysis). The results showed that the cultivars clustered into a main group consisted of nine cultivars (Boni, Bingin, Selem, Embad, Nangka, Penyalin, Maong, Nyuh, and Putih). However, two cultivars (Muani and Gondok) were distinctly separated from this main group and two the others Nanas and Gula were intermediate. The principal component analysis (PCA) revealed that the main group has highly correlated to the characters abaxial cell length and number of cross vein density. Muani cultivar generally had longer adaxial cells, wider guard cells and lower stomatal index than the other cultivars. These three characters strongly influenced the separation of Muani from the others. Similarly, Gondok cultivar generally had wider abaxial cells than the other cultivars that discriminated Gondok clearly from the others. Whereas, the intermediate cultivars (Gula and Nanas) were placed between the main group that consisted of nine cultivars and the two separated cultivars (Muani and Gondok). These cultivars (Gula and Nanas) had intermediate values, which influenced their separations.